Interactive Robot Programing Using Mixed Reality. Issue 22 (2018) - Ostanin, M.; Klimchik, A.
Abstract: The number of robots in industry is increasing every year, they are used to automate various processes. It is necessary to create a system for intuitive and effective interaction between robot and human. This paper represents a system for interactive programming of industrial robots based on Mixed Reality (MR). Microsoft HoloLens glasses were used for immersion in MR. By the developed system, a user without programming skills can assign a task to the manipulator. The main system parts are intuitive geometric path planning, time-optimal trajectory planning, and simulator based on MR. Via MR users are able to interact with robots and the spatial environment through the highly intuitive interface. The system comprises two KUKA robot with different kinematic models, with and without redundancy. The works show features and advantages of the MR-based system comparing to Augmented and Virtual Reality. Experiments on three different path cases show the system performance.